2005
DOI: 10.1161/01.str.0000155732.27333.3c
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cerebral Infarction in Stroke-Prone Spontaneously Hypertensive Rats by Statins Associated With Amelioration of Oxidative Stress

Abstract: Background and Purpose-This study aimed to clarify the effect of statins on spontaneous stroke and to examine the antioxidative effect in artificial transient middle cerebral artery occlusion (tMCAO). Methods-Stroke-prone spontaneous hypertensive rats (SHR-SP) were treated with pitavastatin, atorvastatin, simvastatin, or vehicle for 4 weeks. Physiological parameters, serum lipids, and infarct volumes were examined. The markers for oxidative stresses on lipids and DNA were immunohistochemically detected in vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 9 publications
(9 reference statements)
7
36
0
Order By: Relevance
“…8-hydroxyguanosine (8-OHG) is a reliable and commonly used biomarker for oxidative DNA damage caused by superoxide anion, as shown previously after various forms of brain injury [27][28][29], including ICH [28,30]. Here, 8-OHG-positive cells were detected around the injury site 24 h post-ICH in WT and Nrf2 −/− mice (Fig.…”
Section: Nrf2 Deletion Increases Leukocyte Infiltrationsupporting
confidence: 64%
“…8-hydroxyguanosine (8-OHG) is a reliable and commonly used biomarker for oxidative DNA damage caused by superoxide anion, as shown previously after various forms of brain injury [27][28][29], including ICH [28,30]. Here, 8-OHG-positive cells were detected around the injury site 24 h post-ICH in WT and Nrf2 −/− mice (Fig.…”
Section: Nrf2 Deletion Increases Leukocyte Infiltrationsupporting
confidence: 64%
“…Anti-platelet agents were beneficial in ET-1-evoked infarction (Whitehead et al, 2005a) and in SHR-SP spontaneous strokes (Banfi et al, 2004), in accord with a modest beneficial effect in human lacunar stroke. Lipid-decreasing statin drugs had a beneficial effect on stroke incidence and vessel damage in SHR-SP (Kawashima et al, 2003;Nagotani et al, 2005;Sironi et al, 2005), in keeping with the secondary preventive effect of statins in lacunar stroke.…”
Section: Intervention Studies: Comparison With Human Datasupporting
confidence: 64%
“…12 Similar to our findings on cilostazol, we have previously shown that statin has a pleiotropic antioxidative effect other than a direct cholesterol-lowing effect, resulting in the reduction of stroke volume. [13][14][15] In the present study, we showed a strong reduction in oxidative damage by cilostazol (Figure 4), which accounted for the reduction in spontaneous infarct volume compared with the other antiplatelet drugs (Figure 3). In CSPS 2, it was found that cilostazol is superior to aspirin for preventing stroke and reducing hemorrhagic complications with probable cerebrovascular endothelial protection.…”
Section: Omote Et Al Pleiotropic Effect Of Cilostazol In Shr-spsupporting
confidence: 59%